PENDIDIKAN KARAKTER DALAM PERSPEKTIF PENDIDIKAN ISLAM (RELEVANSI PEMIKIRAN KI HAJAR DEWANTARA DAN IBNU MISKAWAIH) - Nurkhalisyah Nurkhalisyah; Rosichin Mansur; Imam Syafi’i (VICRATINA, 2020)
Character education has been discussed for a long time, but it has not yet made significant changes to the world of education, on the contrary. All elements are expected to be able to work together in resolving this problem. Among parents, theachers and the community can provide exampels and teaching related to character education by looking Ki Hajar Dewantara dan ibnu miskawaih. This study that leads to the thinking of characters through sources such as documentation, books, and journals.